IMPACT OF SUSTAINABILITY PRACTICES ON ORGANIZATIONAL PERFORMANCE: MEDIATING ROLE OF ECONOMIC PERFORMANCE - Muhammad Adnan; Hazrat Younas; Jehanzeb Khan; Abdul Haseeb (International Journal of Contemporary Issues in Social Sciences, 2023)
This study wants to investigate the link between sustainability practices and organizational financial performance through mediator’s economic performance. The population of the current research was banking sector employees. Though purposive sampling technique, 460 respondents were selected. Data from the selected sample was gathered through adapted scale. A total of 235 responses were received. The study ensured validity and reliability of the scale used in this study. It is found that both practices, i.e., sustainability exploration and sustainability exploitation have significant relation with organizational financial performance. Furthermore, economic performance partially mediates the link of sustainability practices and organization performance. The study concluded that organizations need to implement sustainability practices for better financial performance. It is also concluded that organizations should change their approach of sustainability to socio-efficiency and eco-efficiency instead of pollution control only. Discussion, implications, limitations and future research avenues are also highlighted.